Recent Progress in Enhancing Poly(Lactic Acid) Stereocomplex Formation for Material Property Improvement - Luo, Fuhong; Fortenberry, Alexander; Ren, Jie; Qiang, Zhe (Frontiers in Chemistry, 2020)
The production and utilization of polymers have been widely implemented into diverse applications that benefit modern human society, but one of the most valuable properties of polymers, durability, has posed a long-standing environmental challenge from its inception since plastic waste can lead to significant contamination and remains in landfills and oceans for at least hundreds of years. Poly(lactic acid) (PLA) derived from renewable resources provides a sustainable alternative to traditional polymers due to its advantages of comparable mechanical properties with common plastics and biodegradability. However, the poor thermal and hydrolytic stability of PLA-based materials limit their potential for durable applications. Stereocomplex crystallization of enantiomeric poly(l-lactide) (PLLA) and poly(d-lactide) (PDLA) provides a robust approach to significantly enhance material properties such as stability and biocompatibility through strong intermolecular interactions between L-lactyl and D-lactyl units, which has been the key strategy to further PLA applications. This review focuses on discussing recent progress in the development of processing strategies for enhancing the formation of stereocomplexes within PLA materials, including thermal processing, additive manufacturing and solution casting. The mechanisms for enhancing SC formation and resulting material property improvement enabled by each method are discussed in detail. Finally, we also provide the perspectives on current challenges and opportunities for improving the understanding of processing-structure-property relationship in PLA materials that could be beneficial to their wide practical applications for a sustainable society.